(untitled) (Fiep Bulletin - online, 2011)
Cardiovascular diseases are today one of the health problems discussed worldwide. The determining factors are various, and among them the hypercholesterolemia is highlighted, this requiring attention from childhood. The aim of this research was to identify the lipid profile and the comparison between the sexes of pre-teens that present obesity. It is a cross and descriptive research realized with 393 male and female students in the age range between 10 and 14, in the city of Anápolis-GO, that presented abdominal obesity. All laboratory exams were performed in the Santa Casa de Misericórdia of Anápolis-GO. Results: From the total of 210 boys analyzed as to the total cholesterol, 63 are within the desirable values. From the total of 183 girls, 66 are within the desirable levels. As for the triglycerides concentrations, they are within the values considered desirable, 65.71% of the boys and 72.13% of the girls. Referring to the LDL-c, it is within the reference values, 48.57% for the boys and 57.37% for the girls. The variable HDL-c presented itself favorable in 60.65% of the teen-age boys and in 41.42% of the girls. Conclusion: The male sex presented a greater prevalence of hypercholesterolemia than the female sex. We still stress that, due to the incidence of this factor in pre-teens, it is primordial a previous knowledge about the lipid alterations in order that preventive measures be taken early.